Preparation method and application of soft and hard carbon composite negative electrode material

In the preparation of soft and hard carbon composite anode material of sodium ion batteries, the asphalt is coated tightly on the hard carbon precursor by using borohydride salt reduction and preoxidation treatment, which solves the problem of limited performance improvement effect of the negative electrode material in the prior art. , realizes soft and hard carbon composite anode material with high capacity and high circulation performance.

CN117865124BActive Publication Date: 2024-12-17三一红象电池有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410170755.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-06
Publication Date
2024-12-17
Estimated Expiration
2044-02-06

AI Technical Summary

Technical Problem

The negative electrode materials obtained by the existing method of preparing soft and hard carbon composite anode materials of sodium ion batteries have limited effect on improving the charging capacity and circulation performance of the battery, mainly due to the incomplete bond between hard carbon materials and asphalt, resulting in incomplete asphalt coating.

Method used

By mixing the hard carbon precursor with the borohydride brine solution for reduction treatment, adding reducing functional groups, and then mixing the preoxidized asphalt with the reduced hard carbon precursor, the redox effect between the functional groups is used to make the asphalt The hard carbon precursor is coated more tightly and intactly, and finally sintering is carried out to prepare soft and hard carbon composite anode material.

Benefits of technology

The prepared soft and hard carbon composite anode material has high capacity and high circulation performance. The hard carbon material is closely combined with asphalt and has good coating effect, which significantly improves the charging capacity and circulation performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117865124B_ABST
    Figure CN117865124B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of battery technology, and specifically to a method for preparing a soft and hard carbon composite negative electrode material and its application. The method for preparing a soft and hard carbon composite negative electrode material provided by the present invention comprises the following steps: mixing a hard carbon precursor and a borohydride salt aqueous solution and performing a reduction treatment to obtain a hard carbon precursor after the reduction treatment; then mixing the pre-oxidized asphalt and the reduced hard carbon precursor and reacting them to obtain a soft and hard carbon composite precursor; finally, sintering the soft and hard carbon composite precursor to obtain the soft and hard carbon composite negative electrode material. The present invention utilizes the redox reaction between functional groups to make the asphalt more tightly and completely coated on the hard carbon precursor, thereby preparing a high-capacity and high-cycle soft and hard carbon composite negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a preparation method of a soft-hard carbon composite negative electrode material and application thereof. Background Art

[0002] As an effective supplement to lithium-ion batteries, sodium-ion batteries are increasingly attracting people's attention. The negative electrode materials of sodium-ion batteries mainly include carbon materials, phosphides, etc. Among them, carbon materials are generally divided into soft carbon materials and hard carbon materials. Hard carbon materials have many disordered structures and abundant pores. Their specific capacity is high, but their cycle performance is poor. Soft carbon materials such as asphalt have more ordered structural characteristics and fewer defects than hard carbon materials, but the specific capacity of asphalt is lower. Therefore, people think of combining hard carbon materials with asphalt, such as using asphalt to coat hard carbon materials to improve the comprehensive performance of negative electrode materials.

[0003] Existing soft and hard carbon composite negative electrode materials for sodium ion batteries are generally obtained by directly mixing hard carbon precursors and asphalt and then sintering them, or by pre-oxidizing asphalt and then mixing it with hard carbon precursors and sintering them. However, the negative electrode materials obtained by existing processes have limited effect on improving battery charging capacity and cycle performance. Summary of the invention

[0004] The problem to be solved by the present invention is to overcome at least some of the defects of the negative electrode materials obtained by the preparation methods of existing soft and hard carbon composite negative electrode materials, that is, the limited effect on improving the battery charging capacity and cycle performance, and further provide a preparation method for soft and hard carbon composite negative electrode materials and their application.

[0005] In order to achieve the above object, the present invention adopts the following technical scheme:

[0006] The first aspect of the present invention provides a method for preparing a soft and hard carbon composite negative electrode material, comprising the following steps:

[0007] 1) mixing a hard carbon precursor and a borohydride salt aqueous solution and performing a reduction treatment to obtain a hard carbon precursor after the reduction treatment;

[0008] 2) mixing the pre-oxidized asphalt and the reduced hard carbon precursor and reacting them to obtain a soft and hard carbon composite precursor;

[0009] 3) Sintering the soft and hard carbon composite precursor to obtain the soft and hard carbon composite negative electrode material.

[0010] Existing soft and hard carbon composite negative electrode materials for sodium ion batteries are generally obtained by directly mixing a hard carbon precursor and asphalt, and then sintering, or by first pre-oxidizing the asphalt, and then mixing it with the hard carbon precursor and sintering it. However, the negative electrode materials obtained by the existing methods for preparing soft and hard carbon composite negative electrode materials have loose bonds between the hard carbon material and the asphalt, and the asphalt coating is incomplete, which affects the charging capacity and cycle performance of the battery. The present invention utilizes borohydride salt to perform a reduction treatment on the hard carbon precursor, so that reducing functional groups are added to the hard carbon precursor, and oxidizing functional groups are added to the asphalt by pre-oxidation treatment of the asphalt. The present invention cleverly utilizes the redox effect between the functional groups to make the asphalt more tightly and completely coated on the hard carbon precursor, so as to prepare a high-capacity and high-cycle soft and hard carbon composite negative electrode material.

[0011] In an optional embodiment, the reduction treatment temperature in step 1) is 60-90°C, and the reduction treatment time is 1-5h; optionally, the reduction temperature can be 60°C, 65°C, 70°C, 75°C, 80°C, and the reduction treatment time can be 1h, 2h, 3h, 4h, 5h.

[0012] and / or, the borohydride salt in the borohydride salt aqueous solution is selected from at least one of sodium borohydride, potassium borohydride and lithium borohydride, preferably, the borohydride salt in the borohydride salt aqueous solution is selected from sodium borohydride;

[0013] And / or, the mass ratio of the hard carbon precursor to the borohydride salt solution is 1:(10-50), and the concentration of the borohydride salt solution is 0.1-3 mol / L. Optionally, the mass ratio of the hard carbon precursor to the borohydride salt solution is 1:10, 1:20, 1:30, 1:40, 1:50. The concentration of the borohydride salt solution can be 0.1 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L.

[0014] In an optional embodiment, after the reduction treatment is completed, the method further includes filtering the mixed liquid and washing the filter cake with water.

[0015] In an optional embodiment, the preparation method of the hard carbon precursor includes pre-sintering and ball-milling biomass powder to obtain the hard carbon precursor. Optionally, in the present invention, biomass powder is selected as the raw material of the hard carbon precursor, and the hard carbon precursor is obtained by pre-sintering and ball-milling. Preferably, the present invention uses bamboo powder as the raw material of the hard carbon precursor, and utilizes the inherent hollow porous fiber structure characteristics of the bamboo-based material. After carbonization, the hollow porous structure will become a sodium storage site, and combining it with the asphalt after pre-oxidation treatment is conducive to further improving the charging capacity and cycle performance of the battery and improving the coating effect. Further preferably, the present invention uses nanmu bamboo powder as the raw material of the hard carbon precursor. Compared with other bamboo powder raw materials, its pore structure is larger. After carbonization, it serves as a sodium storage site to increase the capacity. At the same time, it can be combined with the asphalt after pre-oxidation treatment to ensure a higher initial charge and discharge efficiency and cycle performance, and also has an excellent coating effect.

[0016] The present invention does not specifically limit the length of the biomass powder. Optionally, the length of the biomass powder is not greater than 1 cm, for example, 0.1-1 cm, and the thickness is not greater than 0.1 cm, for example, 0.01-0.1 cm.

[0017] In an optional embodiment, the pre-sintering temperature is 300-500°C, and the pre-sintering time is 3-5h; optionally, the pre-sintering temperature can be 300°C, 350°C, 400°C, 450°C, 500°C; the pre-sintering time can be 3h, 3.5h, 4h, 4.5h, 5h.

[0018] And / or, the heating rate during the pre-sintering process is 5-10°C / min, and the pre-sintering atmosphere is nitrogen and / or an inert gas atmosphere; optionally, the heating rate during the pre-sintering process may be 5°C / min, 6°C / min, 7°C / min, 8°C / min, 10°C / min. The inert gas may be argon, helium or the like.

[0019] And / or, after the pre-sintering process is completed, the step of cooling the pre-sintered product is also included;

[0020] In an optional embodiment, the present invention does not specifically limit the conditions for ball milling. Optionally, the ball milling speed is 300-500 r / min, the ball milling time is 1-3 h, and the ball-to-material ratio is 1:(2-10).

[0021] And / or, the biomass powder is selected from bamboo powder; preferably, the biomass powder is selected from bamboo powder.

[0022] In an optional embodiment, the mass ratio of the pre-oxidation treated asphalt to the reduction treated hard carbon precursor is (3-16): 100;

[0023] And / or, in step 2), the reaction temperature is 50-100°C, and the reaction time is 3-10 min, preferably the reaction temperature is 60-80°C, and the reaction time is 3-10 min;

[0024] And / or, the reaction in step 2) is carried out in a microwave reactor;

[0025] And / or, in step 3), the sintering temperature is 1300-1600° C. and the sintering time is 3-5 h;

[0026] And / or, in step 3), the sintering atmosphere is nitrogen and / or inert gas, and the sintering heating rate is 5-10°C / min.

[0027] In an optional embodiment, the step 2) further includes dissolving the pre-oxidized asphalt with an organic alcohol before mixing the pre-oxidized asphalt with the reduction-treated hard carbon precursor.

[0028] In an optional embodiment, the organic alcohol is selected from C1-C10 organic alcohols, preferably, the organic alcohol is selected from C1-C5 organic alcohols, and further preferably, the organic alcohol is selected from at least one of methanol, ethanol, and n-propanol;

[0029] And / or, the mass ratio of the pre-oxidation treated asphalt to the organic alcohol is 1:(200-500);

[0030] And / or, after the reaction in step 2) is completed, the step of removing the organic alcohol is also included.

[0031] In an optional embodiment, the method for preparing the pre-oxidized asphalt includes: pre-oxidizing the asphalt in an oxygen-containing atmosphere to obtain the pre-oxidized asphalt.

[0032] In an optional embodiment, the method for preparing the soft and hard carbon composite negative electrode material provided by the present invention comprises the following steps:

[0033] 1) mixing a hard carbon precursor and a borohydride salt aqueous solution and performing a reduction treatment to obtain a hard carbon precursor after the reduction treatment;

[0034] 2) pre-oxidizing the asphalt in an oxygen-containing atmosphere to obtain pre-oxidized asphalt;

[0035] 3) mixing the pre-oxidized asphalt and the reduced hard carbon precursor and reacting them to obtain a soft and hard carbon composite precursor;

[0036] 4) Sintering the soft and hard carbon composite precursor to obtain the soft and hard carbon composite negative electrode material.

[0037] Regarding the selection of the borohydride salt in the borohydride salt aqueous solution, it can be understood that the borohydride salt in the borohydride salt aqueous solution is selected from at least one of sodium borohydride, potassium borohydride and lithium borohydride; preferably, the borohydride salt is selected from sodium borohydride.

[0038] In an optional embodiment, the pre-oxidation treatment temperature is 100-400°C, and the pre-oxidation treatment time is 1-5h; optionally, the pre-oxidation treatment temperature can be 100°C, 150°C, 200°C, 250°C, 300°C; the pre-oxidation treatment time can be 1h, 2h, 3h, 4h, 5h.

[0039] And / or, the pre-oxidation treatment heating rate is 5-10°C / min; the oxygen-containing atmosphere in the present invention can be an oxygen atmosphere or an air atmosphere.

[0040] And / or, after the pre-oxidation treatment is completed, the step of cooling the pre-oxidation product is also included;

[0041] And / or, the asphalt is selected from at least one of natural asphalt, shale asphalt, coal-based asphalt, and petroleum asphalt. And / or, the softening point of the asphalt is 180-280°C, for example, the softening point of the asphalt can be 180°C, 200°C, 250°C, 260°C, and 280°C. The present invention uses asphalt with a specific softening point, which cooperates with the hard carbon precursor to improve the first efficiency and cycle performance of the battery. It can be understood that the softening point of asphalt is the softening point conventionally understood in the art. The test method can be to place the sample in a metal ring of specified size, place a steel ball of specified size and mass on it, place it in water (5°C) or glycerol (32.5°C), and heat it at a rate of 5±0.5°C / min to the temperature when the steel ball sinks to a specified distance (25.4mm), expressed in °C, which to a certain extent represents the temperature stability of the asphalt.

[0042] A second aspect of the present invention provides a sodium ion battery negative electrode material prepared by the above-mentioned preparation method.

[0043] A third aspect of the present invention provides a sodium ion battery, comprising the sodium ion battery negative electrode described above.

[0044] Beneficial effects of the present invention:

[0045] The method for preparing the soft and hard carbon composite negative electrode material provided by the present invention comprises the following steps: firstly, mixing a hard carbon precursor and a borohydride salt aqueous solution and then performing a reduction treatment to obtain a hard carbon precursor after the reduction treatment; then mixing the pre-oxidized asphalt and the reduced hard carbon precursor and reacting them to obtain a soft and hard carbon composite precursor; and finally sintering the soft and hard carbon composite precursor to obtain the soft and hard carbon composite negative electrode material. The present invention uses a borohydride salt to perform a reduction treatment on the hard carbon precursor to add reducing functional groups to the hard carbon precursor, and performs a pre-oxidation treatment on the asphalt to add oxidizing functional groups to the asphalt. The present invention cleverly utilizes the redox reaction between the functional groups to make the asphalt more tightly and completely coated on the hard carbon precursor, so as to prepare a high-capacity and high-cycle soft and hard carbon composite negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0047] Figure 1 This is a SEM image of the soft and hard carbon composite negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0048] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0049] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0050] The petroleum asphalt used in the following Examples 1-7 and Comparative Examples 1-3 was purchased from Dalian Xinde New Material Technology Co., Ltd. and has a softening point of 280°C.

[0051] Example 1

[0052] This embodiment provides a method for preparing a soft and hard carbon composite negative electrode material, comprising the following steps:

[0053] 1) Bamboo powder (bamboo powder length is 0.5 cm, thickness is 0.05 cm) is placed in a calcining furnace for pre-sintering, the pre-sintering temperature is 500 ° C, the pre-sintering time is 3 hours, the heating rate is 5 ° C / min, the pre-sintering atmosphere is nitrogen, and after the pre-sintering treatment is completed, it is naturally cooled to room temperature and taken out to obtain gray-black carbonized fibers. The carbonized fibers are then placed in a ball mill for 2 hours, the ball mill speed is 400 r / min, the ball milling medium and the tank body are agate, the ball-to-material ratio is 1:5, and after the ball milling is completed, it is taken out to obtain a hard carbon precursor;

[0054] 2) mixing a hard carbon precursor and a sodium borohydride aqueous solution (the concentration of the sodium borohydride aqueous solution is 1 mol / L), wherein the mass ratio of the hard carbon precursor to the sodium borohydride aqueous solution is 1:30, and then placing the mixed solution in a polytetrafluoroethylene reactor for reduction treatment, wherein the reduction treatment temperature is 90° C., and the reduction treatment time is 3 h. After the reduction treatment is completed, filtering is performed, and the filter cake is washed with water to obtain a hard carbon precursor after reduction treatment having a reducing group;

[0055] 3) Put the petroleum asphalt into an atmosphere sintering furnace for pre-oxidation treatment, the pre-oxidation temperature is 300°C, the pre-oxidation time is 2h, the pre-oxidation atmosphere is oxygen, the pre-oxidation heating rate is 5°C / min, and after the pre-oxidation treatment is completed, it is naturally cooled to room temperature and taken out to obtain asphalt with oxidizing groups (asphalt after pre-oxidation treatment);

[0056] 4) dissolving 2 g of the asphalt with oxidizing groups obtained in step 3) in 800 g of ethanol, and then adding 18 g of the hard carbon precursor with reducing groups obtained in step 2) after reduction treatment to mix, and placing it in a microwave reactor for heating reaction after mixing, the heating reaction temperature is 80°C, and the heating reaction time is 3 min. Under the action of microwave heating, the hard carbon precursor and the functional groups on the asphalt undergo redox reaction to combine, and the asphalt is then coated on the hard carbon precursor. After the heating reaction is completed, the solvent ethanol in the reaction liquid is removed by rotary evaporation to obtain a soft and hard carbon composite precursor;

[0057] 5) placing the soft and hard carbon composite precursor into an atmosphere calcining furnace for sintering, the sintering atmosphere is nitrogen, the sintering heating rate is 7°C / min, the sintering temperature is 1400°C, the sintering time is 5h, and after the sintering is completed, naturally cool to room temperature and take out to obtain the soft and hard carbon composite negative electrode material.

[0058] Example 2

[0059] This embodiment provides a method for preparing a soft and hard carbon composite negative electrode material, comprising the following steps:

[0060] 1) Bamboo powder (bamboo powder length is 1 cm, thickness is 0.1 cm) is placed in a calcining furnace for pre-sintering, the pre-sintering temperature is 500°C, the pre-sintering time is 5 hours, the heating rate is 10°C / min, the pre-sintering atmosphere is nitrogen, and after the pre-sintering treatment is completed, it is naturally cooled to room temperature and taken out to obtain gray-black carbonized fibers, and then the carbonized fibers are placed in a ball mill for 3 hours, the ball mill speed is 500r / min, the ball milling medium and the tank body are agate, the ball-to-material ratio is 1:10, and after the ball milling is completed, it is taken out to obtain a hard carbon precursor;

[0061] 2) mixing a hard carbon precursor and a sodium borohydride aqueous solution (the concentration of the sodium borohydride aqueous solution is 3 mol / L), wherein the mass ratio of the hard carbon precursor to the sodium borohydride aqueous solution is 1:50, and then placing the mixed solution in a polytetrafluoroethylene reactor for reduction treatment, wherein the reduction treatment temperature is 80° C., and the reduction treatment time is 5 h. After the reduction treatment is completed, filtering is performed, and the filter cake is washed with water to obtain a hard carbon precursor after reduction treatment having a reducing group;

[0062] 3) Put the petroleum asphalt into an atmosphere sintering furnace for pre-oxidation treatment, the pre-oxidation temperature is 400°C, the pre-oxidation time is 5 hours, the pre-oxidation atmosphere is oxygen, the pre-oxidation treatment heating rate is 10°C / min, and after the pre-oxidation treatment is completed, it is naturally cooled to room temperature and taken out to obtain asphalt with oxidizing groups (asphalt after pre-oxidation treatment);

[0063] 4) dissolving 2 g of the asphalt with oxidizing groups obtained in step 3) in 800 g of ethanol, and then adding 28 g of the hard carbon precursor with reducing groups obtained in step 2) after reduction treatment to mix, and placing it in a microwave reactor for heating reaction after mixing, the heating reaction temperature is 80°C, and the heating reaction time is 5 min. Under the action of microwave heating, the hard carbon precursor and the functional groups on the asphalt undergo redox reaction to combine, and the asphalt is then coated on the hard carbon precursor. After the heating reaction is completed, the solvent ethanol in the reaction liquid is removed by rotary evaporation to obtain a soft and hard carbon composite precursor;

[0064] 5) placing the soft and hard carbon composite precursor into an atmosphere calcining furnace for sintering, the sintering atmosphere is nitrogen, the sintering heating rate is 10°C / min, the sintering temperature is 1600°C, the sintering time is 5h, and after the sintering is completed, naturally cool to room temperature and take out to obtain the soft and hard carbon composite negative electrode material.

[0065] Example 3

[0066] This embodiment provides a method for preparing a soft and hard carbon composite negative electrode material, comprising the following steps:

[0067] 1) Put bamboo powder (bamboo powder length is 0.8cm, thickness is 0.1cm) into a calcining furnace for pre-sintering, the pre-sintering temperature is 300℃, the pre-sintering time is 3h, the heating rate is 5℃ / min, the pre-sintering atmosphere is argon, and after the pre-sintering treatment is completed, it is naturally cooled to room temperature and taken out to obtain gray-black carbonized fiber, and then the carbonized fiber is put into a ball mill for 1 hour, the ball mill speed is 300r / min, the ball milling medium and the tank body are agate, the ball-to-material ratio is 1:2, and after the ball milling is completed, it is taken out to obtain a hard carbon precursor;

[0068] 2) mixing a hard carbon precursor and a sodium borohydride aqueous solution (the concentration of the sodium borohydride aqueous solution is 0.1 mol / L), wherein the mass ratio of the hard carbon precursor to the sodium borohydride aqueous solution is 1:10, and then placing the mixed solution in a polytetrafluoroethylene reactor for reduction treatment, wherein the reduction treatment temperature is 60° C., and the reduction treatment time is 1 h. After the reduction treatment is completed, filtering is performed, and the filter cake is washed with water to obtain a hard carbon precursor after reduction treatment having a reducing group;

[0069] 3) Put the petroleum asphalt into an atmosphere sintering furnace for pre-oxidation treatment, the pre-oxidation temperature is 100°C, the pre-oxidation time is 1h, the pre-oxidation atmosphere is oxygen, the pre-oxidation heating rate is 5°C / min, and after the pre-oxidation treatment is completed, it is naturally cooled to room temperature and taken out to obtain asphalt with oxidizing groups (asphalt after pre-oxidation treatment);

[0070] 4) dissolving 2 g of the asphalt with oxidizing groups obtained in step 3) in 800 g of ethanol, and then adding 13.3 g of the hard carbon precursor with reducing groups obtained in step 2) after reduction treatment to mix, and placing it in a microwave reactor for heating reaction after mixing, the heating reaction temperature is 60°C, and the heating reaction time is 10 min. Under the action of microwave heating, the hard carbon precursor and the functional groups on the asphalt undergo redox reaction to combine, and the asphalt is then coated on the hard carbon precursor. After the heating reaction is completed, the solvent ethanol in the reaction liquid is removed by rotary evaporation to obtain a soft and hard carbon composite precursor;

[0071] 5) placing the soft and hard carbon composite precursor into an atmosphere calcining furnace for sintering, the sintering atmosphere is argon, the sintering heating rate is 5°C / min, the sintering temperature is 1300°C, the sintering time is 3h, and after the sintering is completed, naturally cool to room temperature and take out to obtain the soft and hard carbon composite negative electrode material.

[0072] Example 4

[0073] This embodiment provides a method for preparing a soft and hard carbon composite negative electrode material, which is different from Embodiment 1 in that in step 1), the bamboo powder is replaced with peanut shell powder.

[0074] Example 5

[0075] This embodiment provides a method for preparing a soft-hard carbon composite negative electrode material, which is different from Embodiment 1 in that in step 1), the bamboo powder is replaced with square bamboo powder.

[0076] Example 6

[0077] This embodiment provides a method for preparing a soft and hard carbon composite negative electrode material, which differs from Embodiment 1 in that in step 2), the sodium borohydride aqueous solution is replaced with a potassium borohydride aqueous solution.

[0078] Example 7

[0079] This embodiment provides a method for preparing a soft and hard carbon composite negative electrode material, which differs from Embodiment 1 in that in step 2), the sodium borohydride aqueous solution is replaced with a lithium borohydride aqueous solution.

[0080] Example 8

[0081] This embodiment provides a method for preparing a soft and hard carbon composite negative electrode material, which differs from Embodiment 1 in that in step 3), petroleum asphalt (softening point is 280°C) is replaced with petroleum asphalt (softening point is 250°C, purchased from Dalian Xinde New Materials Technology Co., Ltd.).

[0082] Example 9

[0083] This embodiment provides a method for preparing a soft and hard carbon composite negative electrode material, which differs from Embodiment 1 in that in step 3), petroleum asphalt (softening point is 280°C) is replaced with petroleum asphalt (softening point is 180°C, purchased from Dalian Xinde New Materials Technology Co., Ltd.).

[0084] Comparative Example 1

[0085] This comparative example provides a method for preparing a soft and hard carbon composite negative electrode material, comprising the following steps:

[0086] 1) Bamboo powder (bamboo powder length is 0.5 cm, thickness is 0.05 cm) is placed in a calcining furnace for pre-sintering, the pre-sintering temperature is 500 ° C, the pre-sintering time is 3 hours, the heating rate is 5 ° C / min, the pre-sintering atmosphere is nitrogen, and after the pre-sintering treatment is completed, it is naturally cooled to room temperature and taken out to obtain gray-black carbonized fibers. The carbonized fibers are then placed in a ball mill for 2 hours, the ball mill speed is 400 r / min, the ball milling medium and the tank body are agate, the ball-to-material ratio is 1:5, and after the ball milling is completed, it is taken out to obtain a hard carbon precursor;

[0087] 2) dissolving 2 g of petroleum asphalt in 800 g of ethanol, adding 18 g of the hard carbon precursor obtained in step 1) and mixing, and then placing the mixture in a microwave reactor for heating at 80° C. for 3 min. After heating, removing the solvent ethanol in the reaction solution by rotary evaporation to obtain a soft and hard carbon composite precursor;

[0088] 3) placing the soft and hard carbon composite precursor into an atmosphere calcining furnace for sintering, the sintering atmosphere is nitrogen, the sintering heating rate is 7°C / min, the sintering temperature is 1400°C, the sintering time is 5h, and after the sintering is completed, naturally cool to room temperature and take out to obtain the soft and hard carbon composite negative electrode material.

[0089] Comparative Example 2

[0090] This comparative example provides a method for preparing a soft and hard carbon composite negative electrode material, comprising the following steps:

[0091] 1) Bamboo powder (bamboo powder length is 0.5 cm, thickness is 0.05 cm) is placed in a calcining furnace for pre-sintering, the pre-sintering temperature is 500 ° C, the pre-sintering time is 3 hours, the heating rate is 5 ° C / min, the pre-sintering atmosphere is nitrogen, and after the pre-sintering treatment is completed, it is naturally cooled to room temperature and taken out to obtain gray-black carbonized fibers. The carbonized fibers are then placed in a ball mill for 2 hours, the ball mill speed is 400 r / min, the ball milling medium and the tank body are agate, the ball-to-material ratio is 1:5, and after the ball milling is completed, it is taken out to obtain a hard carbon precursor;

[0092] 2) Put the petroleum asphalt into an atmosphere sintering furnace for pre-oxidation treatment, the pre-oxidation temperature is 300°C, the pre-oxidation time is 2h, the pre-oxidation atmosphere is oxygen, the pre-oxidation heating rate is 5°C / min, and after the pre-oxidation treatment is completed, it is naturally cooled to room temperature and taken out to obtain asphalt with oxidizing groups (asphalt after pre-oxidation treatment);

[0093] 3) dissolving 2 g of the asphalt with oxidizing groups obtained in step 2) in 800 g of ethanol, and then adding 18 g of the hard carbon precursor obtained in step 1) to mix, and then placing the mixture in a microwave reactor for heating at 80° C. for 3 min. After heating, the solvent ethanol in the reaction solution is removed by rotary evaporation to obtain a soft and hard carbon composite precursor;

[0094] 4) placing the soft and hard carbon composite precursor into an atmosphere calcining furnace for sintering, the sintering atmosphere is nitrogen, the sintering heating rate is 7°C / min, the sintering temperature is 1400°C, the sintering time is 5h, and after the sintering is completed, naturally cool to room temperature and take out to obtain the soft and hard carbon composite negative electrode material.

[0095] Comparative Example 3

[0096] This comparative example provides a method for preparing a soft and hard carbon composite negative electrode material, comprising the following steps:

[0097] 1) Bamboo powder (bamboo powder length is 0.5 cm, thickness is 0.05 cm) is placed in a calcining furnace for pre-sintering, the pre-sintering temperature is 500 ° C, the pre-sintering time is 3 hours, the heating rate is 5 ° C / min, the pre-sintering atmosphere is nitrogen, and after the pre-sintering treatment is completed, it is naturally cooled to room temperature and taken out to obtain gray-black carbonized fibers. The carbonized fibers are then placed in a ball mill for 2 hours, the ball mill speed is 400 r / min, the ball milling medium and the tank body are agate, the ball-to-material ratio is 1:5, and after the ball milling is completed, it is taken out to obtain a hard carbon precursor;

[0098] 2) placing the hard carbon precursor in a nitrogen-hydrogen mixed gas atmosphere (nitrogen accounts for 95% by volume and hydrogen accounts for 5% by volume in the nitrogen-hydrogen mixed gas) for reduction treatment at a temperature of 400° C. for a reduction treatment time of 3 h to obtain a hard carbon precursor after reduction treatment;

[0099] 3) Put the petroleum asphalt into an atmosphere sintering furnace for pre-oxidation treatment, the pre-oxidation temperature is 300°C, the pre-oxidation time is 2h, the pre-oxidation atmosphere is oxygen, the pre-oxidation heating rate is 5°C / min, and after the pre-oxidation treatment is completed, it is naturally cooled to room temperature and taken out to obtain asphalt with oxidizing groups (asphalt after pre-oxidation treatment);

[0100] 4) dissolving 2 g of the asphalt with oxidizing groups obtained in step 3) in 800 g of ethanol, and then adding 18 g of the hard carbon precursor obtained in step 2) after reduction treatment to mix, and then placing it in a microwave reactor for heating at a temperature of 80° C. for 3 min. After the heating is completed, the solvent ethanol in the reaction solution is removed by rotary evaporation to obtain a soft and hard carbon composite precursor;

[0101] 5) placing the soft and hard carbon composite precursor into an atmosphere calcining furnace for sintering, the sintering atmosphere is nitrogen, the sintering heating rate is 7°C / min, the sintering temperature is 1400°C, the sintering time is 5h, and after the sintering is completed, naturally cool to room temperature and take out to obtain the soft and hard carbon composite negative electrode material.

[0102] Test Case

[0103] The soft and hard carbon composite negative electrode material prepared in the embodiment or comparative example, the conductive agent Ketjen black, the binder sodium carboxymethyl cellulose, styrene-butadiene rubber, and water were mixed in a mass ratio of 94:1.5:1.5:3:100 to obtain a slurry, and then the slurry was coated on an aluminum foil, and after drying and rolling, a surface density of 6 mg / cm 2 , compacted density is 1mg / cm 3The sodium ion battery hard carbon electrode (the coating effect is shown in Table 1) was prepared by using a sodium sheet as the counter electrode, glass fiber as the diaphragm, the electrolyte solute was 1 mol / L NaPF6, and the solvent was composed of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1. The CR2032 button-type sodium ion battery was assembled in an argon-filled glove box.

[0104] The electrochemical performance of the CR2032 button sodium ion battery was tested in the voltage range of 0-2V and at a current density of 0.1C. The first charge capacity and first efficiency, as well as the capacity retention rate after 100 cycles at a rate of 1C were recorded. The test results are shown in Table 1.

[0105] Table 1

[0106]

[0107]

[0108] The present invention uses borohydride salt to reduce the hard carbon precursor, then mixes the pre-oxidized asphalt and the reduced hard carbon precursor and reacts them to obtain a soft and hard carbon composite precursor, and finally sinters the soft and hard carbon composite precursor to obtain a soft and hard carbon composite negative electrode material, which is applied to the battery. It can be seen from Example 1 and Comparative Examples 1-3 that the first charging capacity, capacity retention rate after 100 cycles, first efficiency and coating effect of Example 1 are better than those of Comparative Examples 1-3. In addition, it can be seen from the comparison of Example 1 and Example 4 or Example 5 that the present invention uses bamboo powder as the raw material of the hard carbon precursor, which is better than other biomass raw materials such as peanut shell powder or other bamboo powder in improving the charging capacity, cycle performance or coating performance of the battery.

[0109] The soft and hard carbon composite negative electrode material prepared by the preparation method of the present invention has a tight combination of hard carbon material and asphalt, complete asphalt coating, and good coating effect. The soft and hard carbon composite negative electrode material assembled in the battery has high charging capacity, strong cycle performance, and high first efficiency. In particular, the soft and hard carbon composite negative electrode material is prepared using nanmu powder as the raw material of the hard carbon precursor, and its effect is better.

[0110] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for preparing a soft and hard carbon composite negative electrode material, characterized in that: The steps include: 1) mixing a hard carbon precursor and a borohydride salt aqueous solution and performing a reduction treatment to obtain a hard carbon precursor after the reduction treatment; The method for preparing the hard carbon precursor comprises pre-sintering and ball-milling biomass powder to obtain the hard carbon precursor; The reduction treatment temperature is 60-90° C., the reduction treatment time is 1-5 h, the mass ratio of the hard carbon precursor to the borohydride salt solution is 1:(10-50), and the concentration of the borohydride salt solution is 0.1-3 mol / L; The biomass powder is selected from bamboo powder; 2) mixing the pre-oxidized asphalt and the reduced hard carbon precursor and reacting them to obtain a soft and hard carbon composite precursor; The mass ratio of the pre-oxidized asphalt to the reduced hard carbon precursor is (3-16):100, the reaction temperature is 50-100°C, the reaction time is 3-10min, and the reaction is carried out in a microwave reactor; The method for preparing the pre-oxidized asphalt comprises pre-oxidizing the asphalt in an oxygen-containing atmosphere to obtain the pre-oxidized asphalt, wherein the pre-oxidation temperature is 100-400° C. and the pre-oxidation time is 1-5 hours; 3) Sintering the soft and hard carbon composite precursor to obtain the soft and hard carbon composite negative electrode material.

2. The method for preparing the negative electrode material according to claim 1, characterized in that: The borohydride salt in the borohydride salt aqueous solution in step 1) is selected from at least one of sodium borohydride, potassium borohydride and lithium borohydride.

3. The method for preparing the negative electrode material according to claim 2, characterized in that: The borohydride salt in the borohydride salt aqueous solution is selected from sodium borohydride.

4. The method for preparing the negative electrode material according to claim 1, characterized in that: The pre-sintering temperature is 300-500°C, and the pre-sintering time is 3-5h; And / or, the heating rate during the pre-sintering process is 5-10°C / min, and the pre-sintering atmosphere is nitrogen and / or an inert gas atmosphere; And / or, the ball milling speed is 300-500 r / min, the ball milling time is 1-3 h, and the ball-to-material ratio is 1:(2-10).

5. The method for preparing the negative electrode material according to claim 1, characterized in that: In step 3), the sintering temperature is 1300-1600° C. and the sintering time is 3-5 hours; And / or, in step 3), the sintering atmosphere is nitrogen and / or inert gas, and the sintering heating rate is 5-10°C / min.

6. The method for preparing the negative electrode material according to claim 1, characterized in that: In step 2), the pre-oxidized asphalt is further comprised of dissolving the pre-oxidized asphalt with an organic alcohol before being mixed with the reduced hard carbon precursor.

7. The method for preparing the negative electrode material according to claim 1 or 6, characterized in that: The pre-oxidation treatment heating rate is 5-10°C / min; And / or, the asphalt is selected from at least one of natural asphalt, shale asphalt, coal-based asphalt, and petroleum asphalt; And / or, the softening point of the asphalt is 180-280°C.

8. A sodium ion battery negative electrode material, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 7.

9. A sodium ion battery, characterized in that: Including the sodium ion battery negative electrode material as described in claim 8.

Citation Information

Patent Citations

  • Negative electrode material and preparation method thereof, battery negative electrode and lithium ion battery

    CN113422030A

  • Carbon negative electrode material and preparation method thereof, lithium ion battery negative electrode, lithium ion battery and electric equipment

    CN115377414A

  • Asphalt-based soft carbon composite cellulose hard carbon negative electrode material and preparation method thereof

    CN115744872A

  • Preparation method and application of soft carbon / hard carbon composite material

    CN116675215A

  • Preparation method and preparation device of hard carbon negative electrode material

    CN116789102A